Robotic Process Automation and effectiveness of financial decisions: A critical review - Susan Otaru; Umaru Zubairu; Grace Bikefe; Yakubu Mustapha; Simeon Araga; Afisat Ayorinde (Journal of Innovation in Business and Economics, 2020)
Robotic Process Automation (RPA) has emerged over the last decade as an important tool for improving the effectiveness of many financial decisions through automation of several everyday financial tasks. According to optimists, this is a good thing for business. However, the skeptics believe that RPA will likely lead to a replacement of humans with machines. This study conducted a critical review of existing RPA empirical studies to shed more light on which party of the RPA debate is most supported by the evidence. The empirical evidence showed that RPA adoption leads to improved productivity and significant returns on investment. However, there is a need for a significant number of empirical studies to be carried out over the coming years before the RPA debate can be definitively settled.